Analysis of Freedom of Expression in the Digital Age in the Issue of Electronic Information and Transaction Law in Indonesia - Tommi Imanuel; Warjio; Indra Fauzan (Universitas Medan Area, 2023)
This research is to analyze freedom of expression in the digital era in Indonesia and to analyze the problems of the Electronic Information and Transaction Law regarding freedom of expression in Indonesia. The research method used in this research is library research. In this study, the authors used a qualitative research approach. A qualitative research approach allows researchers to explore and analyze issues related to freedom of expression in the digital era in greater depth. This research uses SWOT analysis to identify strengths, weaknesses, opportunities and threats that are relevant in the context being studied through documents related to freedom. expression and the ITE Law in Indonesia. Analyzing data by identifying the main themes or finding patterns that appear in relevant journals or articles. The results of this research explain how important freedom of expression is in the digital era which has the potential to be a force for society in conveying opinions and views openly and freely. This can strengthen democracy and generate constructive criticism of government policies, as well as the policies of other institutions. freedom of expression by utilizing advances in digital technology in the current digital era provides opportunities for the community to maximize its role as government control. Freedom of opinion in the digital era is also regulated by Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions which provide further protection for privacy and user personal data in the digital era.